Potential value of repeat stool testing for Clostridium difficile stool toxin using enzyme immunoassay? - Deshpande, Abhishek; Pasupuleti, Vinay; Pant, Chaitanya; Hall, Geraldine; Jain, Anil (Current Medical Research & Opinion, 2010)
OBJECTIVE: The aim of this brief review is to summarize the literature as it relates to the potential value of repeat stool testing for Clostridium difficile (C. difficile) toxin using an enzyme immunoassay (EIA) for toxin A&B and also propose a potential newer algorithm for diagnosing C. difficile. RESEARCH DESIGN AND METHODS: Two investigators conducted independent literature searches using PubMed, Web of Science, and Scopus until May 1st, 2010. All databases were searched using the terms Clostridium difficile, CDAD, antibiotic associated diarrhea, C. difficile in combination with enzyme immunoassay, enzyme linked immunosorbent assay, Clostridium difficile toxin A, Clostridium difficile toxin B, Clostridium difficile toxin and repeat stool testing. Articles which discussed EIA in C. difficile infection (CDI) patients were reviewed and relevant cross references also read and evaluated for inclusion. Selection bias could be a possible limitation of the approach used in selecting or finding articles for this article. FINDINGS: The evidence for repeat stool testing for C. difficile toxin detection using toxin EIA is becoming weaker. Most recent published practice guidelines recommend a two- or three-step testing algorithm for the detection of C. difficile. CONCLUSIONS: EIA for C. difficile stool toxin has a limited sensitivity, but, it does not warrant repeat stool testing. The data for this are suggestive but not conclusive. More studies and better tests are needed to have clear guidelines which can specify the number of tests needed in a diagnostic workup of suspected C. difficile infection. A two-step or three-step method in the diagnosis of C. difficile-associated diarrhea offered a marked increase in sensitivity compared to that of toxin A&B EIA alone.